The Influence of Work Culture and Remuneration on Employee Performance At Pt. X In Cikarang, Indonesia - Hadi, Rachman; Anwar, Ravel (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Employee performance is a key element in determining the success and competitiveness of a company in the global market. This research aims to identify and analyze the influence of work culture and the remuneration system on employee performance at PT. X in Cikarang, Indonesia. X in Cikarang, Indonesia. X in Cikarang, Indonesia. The research method used is a descriptive correlational design with a stratified random sampling technique, resulting in a sample of 51 employees. The data analysis technique employs multiple linear regression to evaluate the simultaneous influence of work culture and remuneration on employee performance. The study's results indicate that work culture significantly influences employee performance, with a beta coefficient of 0.443 and a significance of 0.000. Remuneration also influences employee performance with a beta coefficient of 0.324 and a significance of 0.003. The combination of work culture and remuneration explains 49.8% of the variability in employee performance, with an R Square value of 0.498 and an F value of 15.572 (p < 0.001). The conclusion of this study underscores the importance of synergy between a positive work culture and a fair remuneration system to enhance employee performance. The study's practical recommendations, including the development of work culture strategies that support collaboration and openness and a comprehensive review of the remuneration system to ensure competitive salary scales, benefits, and bonuses, will guide and empower the audience in their efforts to enhance employee performance. Further research is suggested to explore other variables, such as leadership, training, and career development, and to conduct longitudinal studies to understand performance changes over time. This emphasis on continuous learning and improvement will make the audience feel the importance of staying updated with the latest research in the field.